Population-based incidence of hospitalized Clostridioides difficile infection among older adults in Ota-ku, Japan: A prospective surveillance study. (August 2022) - Tateda, Kazuhiro; Ishida, Junro; Ito, Shuhei; Gonzalez, Elisa; Yoshizumi, Satoshi; Zhang, Pingping; Pride, Michael; Gray, Sharon; Ferreira, Cátia Matos; Minarovic, Nadia; Angulo, Frederick J.; Moïsi, Jennifer C.; et al.
Abstract: Objectives: Clostridioides difficile infection (CDI) burden is not well-characterized in Japan. Therefore, we conducted a population-based, hospitalized CDI incidence study, compared the results with standard-of-care (SOC) CDI testing, and generalized the results for nationwide incidence estimates. Methods: Surveillance identified inpatients ≥50 years-of-age with diarrhea in nine Tokyo hospitals from December 17, 2018–March 30, 2020. A CDI case was defined as a patient with a PCR-positive/cell cytotoxicity neutralization assay (CCNA)-positive stool or a PCR-positive stool and pseudomembranous colitis (PMC). Incidence estimates were adjusted for the hospitalization share of participating hospitals and, in the sensitivity analysis, for missing CDI test results. SOC specimen collection and CDI testing occurred independently. Results: Surveillance during 318 840 patient-days identified 4633 inpatients with diarrhea. Sixty-three CDI cases were identified; 11 (17·5%) had PMC, eight (12·7%) recurrent CDI, and nine (14·3%) died. The hospitalized CDI incidence was 97/100 000 population per year (PPY) in persons ≥50 years-of-age and, in the sensitivity analysis, 324/100 000 PPY. The incidence was 170 and 481/100 000 PPY in persons ≥65 and ≥85 years-of-age, respectively; these estimates increased to 569 and 1609/100 000 PPY in the sensitivity analysis, respectively. There were 12 primary SOC CDI cases in persons ≥50 years-of-age (18/100 000 PPY). Conclusions: The CDI incidence was high in older adults, with severe clinical consequences. SOC specimen collection and testing under-estimated CDI burden. There are >57 000 hospitalized CDI cases per year in Japan in persons ≥50 years-of-age. Public health interventions are needed to reduce the CDI burden in Japan. Highlights: Population-based incidence study of hospitalized C. difficile infection (CDI) in Japan. Hospitalized CDI incidence was high in adults aged ≥50 years and increased with age. A high proportion of CDI patients had severe clinical consequences, including death. Standard-of-care stool specimen collection and testing under-diagnosed CDI burden. Effective prevention strategies are needed to reduce CDI burden in Japan.